Cracking directions in multiaxial low cycle fatigue at high and room temperatures (Fracture and Structural Integrity, 2017)
Cracking direction in multiaxial low cycle fatigue is an important research subject because crack initiation and propagation behavior is a physical background for developing an estimation method of multiaxial low cycle fatigue lives. However, there are a few open questions on cracking direction in multiaxial low cycle fatigue because cracking direction in multiaxial low cycle fatigue is complex and changes depending on stress multiaxiality, strain range, notch and material. This paper overviews cracking directions in tension-torsion low cycle fatigue of low alloy steels and nickel base superalloys. Two types of cracking directions in these materials, maximum shear direction and maximum principal direction, are discussed in relation with strain multiaxiality and an existence of notch and precrack. The two cracking directions in torsion low cycle fatigue of SUS 304 stainless steel are also discussed in relation with strain range. Detailed micro crack observations are finally presented to discuss the two cracking directions in torsion low cycle fatigue of a SUS 304 unnotched specimen.
Keywords: Multiaxial fatigue; Crack mode; Notch; Fatigue life; Torsion